Free Nutritious Meal Policy Through the Philosophical Lenses of Foucault and Al-Attas - Anugrah Presisi Putra Gumay; Rustam Ibrahim (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2026)
The Free Nutritious Meal (MBG) policy in Indonesia is widely glorified from a technocratic-pragmatic stance as an instrument for stunting mitigation and human capital acceleration. However, this massive materialistic intervention risks reducing the ontological essence of students and shifting the sublime function of educational institutions. Previous studies have been heavily dominated by administrative, logistical, and clinical evaluations, thereby neglecting the philosophical implications of state somatic intervention in schools. This qualitative library research, employing a comparative philosophical design, aims to critically examine the MBG policy through the critical apparatus of Michel Foucault’s biopolitics and Syed Muhammad Naquib al-Attas’s epistemology of ta’dib. Analyzed through the dimensions of ontology, epistemology, and axiology, the results indicate that: (1) from a Foucauldian lens, the MBG policy operates as a biopolitical machine utilizing medical power/knowledge relations to transform classrooms into disciplined spaces for reproducing docile bodies to serve global industrial markets; (2) from al-Attas’s perspective, the absolutism of physical indicators (al-nafs al-hayawaniyyah) triggers the secularization of education (deconsecration of values), sidelining spiritual nutrition and worsening moral decadence. This study synthesizes both thoughts into the "Somatic-Based Civilizational Paradigm," a school feeding policy blueprint that positions physical intake merely as a secondary material means for elevating the rational-spiritual soul of students (al-nafs al-natiqah).